Electronic contribution to the quality factor of ZT for Heusler alloys and unmodified BiCuSeO - Абуова, А.У.; Абуова, Ф.У.; Акилбеков, А.Т.; Джунисбекова, Д.А.; Бақтыбаева, Д. (BULLETIN OF THE L.N. GUMILYOV EURASIAN NATIONAL UNIVERSITY. PHYSICS. ASTRONOMY SERIES, 2022)
In this paper we give a brief description of the theory of the density functional and the transport theory of Boltzmann with respect to the computation of transport coefficients. On the example of Heusler alloys, it was shown that the method of calculating thermoelectric coefficients described in this work is correct and agrees well with experiment and other theoretical calculations. With the help of first-principles methods, the optimal level of doping, predicted earlier by Yabuuchi et al. the corresponding levels were confidently tested and showed excellent thermoelectric behavior.